2002
DOI: 10.1207/s15548430jlr3401_5
|View full text |Cite
|
Sign up to set email alerts
|

Dialogic Responsiveness: Toward Synthesis, Complexity, and Holism in Our Reponses to Young Literacy Learners

Abstract: As children enter classroom literacy contexts, they are not at one moment a cognitive being and at another moment an emotional being, and at yet another moment a cultural being. Children come to us as whole beings with complexities that include cognitive, emotional, cultural, motivational, and even physical needs. Although we have research to suggest ways in which educators can be responsive to these singular needs, we have little research to suggest how educators can be responsive to the whole child in litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…For instance, McCarthey (1998) discovered that students readjusted their participation in relation to peers and in relation to aspects of the curriculum. Likewise, in my research (Triplett, 2002), I discovered that a student acted literate and engaged in one context and acted illiterate and disengaged in another solely in relation to the teacher. Hagood's (2002) research revealed that some students exhibit agency in their social interactions at school, including choosing how they will participate in school literacy contexts.…”
Section: The Social Construction Of Subjectivities and Identitiesmentioning
confidence: 87%
“…For instance, McCarthey (1998) discovered that students readjusted their participation in relation to peers and in relation to aspects of the curriculum. Likewise, in my research (Triplett, 2002), I discovered that a student acted literate and engaged in one context and acted illiterate and disengaged in another solely in relation to the teacher. Hagood's (2002) research revealed that some students exhibit agency in their social interactions at school, including choosing how they will participate in school literacy contexts.…”
Section: The Social Construction Of Subjectivities and Identitiesmentioning
confidence: 87%
“…Hasil studi PISA tahun 2015 yang menunjukkan Indonesia baru bisa menduduki peringkat 69 dari 76 negara. Literasi sains yang diuji dikaitkan dengan keyakinan tentang sifat dan asal pengetahuan ilmiah, harapan karir terkait sains bagi siswa, dan motivasi belajar sains (Triplett, 2002).…”
Section: Pendahuluanunclassified
“…Firstly, reading class is rarely preceded by the process of predicting the content of the reading through asking and answering questions activity. This is resulted from the insufficient learning materials available [8]. Secondly, reading comprehension materials used in the 4th grade of Elementary School could not help the students to imagine what is being read because reading comprehension techniques are not inserted in.…”
Section: Introductionmentioning
confidence: 99%